PENENTUAN FAKTOR BEBAN DINAMIS PADA JEMBATAN BERDASARKAN PENGUKURAN BRIDGE WEIGH-IN-MOTION - Nugraha, Widi; Sidi, Indra Djati; Suarjana, Made; Zulkifli, Ediansjah (Direktorat Bina Teknik Jalan dan Jembatan, 2023)
Vehicle loading on bridges involves dynamic loads, exhibiting distinct behavior from static loads. Dynamic loads can lead to the phenomenon of dynamic load amplification, potentially increasing the effects of the static weight of vehicles on the bridge. Addressing these effects is crucial during bridge design to ensure safety. The Dynamic Amplification Factor (DAF) is employed in bridge design as a multiplier for the live load standard to account for these effects. This study aims to assess the DAF on two Bridge Weigh-in-Motion (B-WIM) systems in Indonesia: Pawiro Baru Bridge (ID-001) with an 18 m in span and Kaligawe Bridge (ID-004) with a 30 m in span. The methodology involves analyzing the bridge's structural response to passing vehicles using strain transducer sensors in the B-WIM system to calculate the DAF. Results indicate that the average DAF for light vehicles (GVW<25 ton) is 1.19 for ID-001 and 1.19 for ID-004. For heavy vehicles (GVW>=25 ton), it's 1.10 for ID-001 and 1.09 for ID-004. The analysis reveals a consistent correlation between DAF and GVW, with heavier vehicles yielding lower DAF values. This research suggests to a proposed DAF model as a function of GVW, which proved to be more efficient and accurate based on actual measurements. The model presents the potential to enhance the efficiency of bridge design. It generally yields lower DAF values compared to those stated in SNI 1725:2016, aiming to align design standards more closely with the actual dynamic behaviour of typical bridge types under varying vehicle loads. Keywords: bridge, dynamic amplification factor (DAF), Bridge Weigh-in-Motion (B-WIM), bridge design, gross vehicle weight (GVW)